Cone beam computed tomography findings of ectopic tooth in the maxillary sinus associated with dentigerous cyst: A report of two cases and review of the literature - Elif Sogur; Meltem Özden; Tayfun Günbay; Zuhal Tugsel (Wolters Kluwer Medknow Publications, 2015)
Dentigerous cysts are the most common type of benign odontogenic lesions that associated with the crown of an unerupted or impacted tooth. They constitute the second most common cystic lesion of the jaws, after radicular cysts. Dentigerous cyst surrounding impacted teeth often displace these teeth into ectopic positions. Ectopic eruption of teeth into regions other than the oral cavity is common but dentigerous cysts associated with ectopic teeth within the maxillary sinus are fairly rare. The diagnosis is usually made by panoramic radiography. Cone beam computed tomography (CBCT) is indicated when an ectopic tooth is associated with an antral mass and prior to surgery. The standard treatment for a dentigerous cyst is enucleation and extraction of the cyst-associated impacted or unerupted tooth. We report CBCT findings of two cases of dentigerous cyst associated with an ectopic tooth in the maxillary sinus and review the literature reports of this condition over the past 34 years.